2018
DOI: 10.3892/ol.2018.7905
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, phase II clinical trial of peptide vaccination with oral chemotherapy following curative resection for stage�III colorectal cancer

Abstract: The safety and immunological responsiveness of a peptide vaccine of ring finger protein 43 and 34-kDa translocase of the outer mitochondrial membrane combined with uracil-tegafur/leucovorin (UFT/LV) was previously demonstrated in metastatic colorectal cancer (CRC) in a phase I clinical trial. To clarify the survival benefit of a peptide vaccine combined with UFT/LV as adjuvant treatment, a phase II clinical trial was conducted involving patients with stage III CRC. All enrolled patients, whose human leukocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…Approximately 70% of the patients in this trial showed specific CTL induction to each of the peptides. This finding is superior to those of previous reports [3][4][5]32]. Additionally, patients receiving dose level 3 (1.0 mg hLAG-3Ig + 1.4 mg Poly-ICLC/injection) had significantly faster and stronger peptide-specific CTL induction than those at dose levels 1 and 2.…”
Section: Discussioncontrasting
confidence: 72%
“…Approximately 70% of the patients in this trial showed specific CTL induction to each of the peptides. This finding is superior to those of previous reports [3][4][5]32]. Additionally, patients receiving dose level 3 (1.0 mg hLAG-3Ig + 1.4 mg Poly-ICLC/injection) had significantly faster and stronger peptide-specific CTL induction than those at dose levels 1 and 2.…”
Section: Discussioncontrasting
confidence: 72%
“…Interestingly, only one patient failed to mount specific CD8 T cell responses against RNF43 and/or TOMM34 and 83% of patients had stable disease following the vaccination (165). After having demonstrated the safety and immunological responsiveness of this combination therapy, the same group showed that 3-years DFS was significantly better in the group of patients with CD8 T cell responses than in the group without (154,166). In order to improve clinical responses, Okuno et al added to this original combination therapy 5 other TAA-derived peptides to the vaccine.…”
Section: Tumor-associated Antigens and Neoantigens In Crc Vaccinationmentioning
confidence: 97%
“…In addition to depending on TAAs, vaccine immunogenicity also relies on the use of adjuvants that are crucial components to boost and enhance antigen-specific immune responses. Most TAA-based vaccines described above are combined with different adjuvants inducing the activation and recruitment of APCs (168), such as incomplete Freund's adjuvant (IFA) (165)(166)(167), TLR-3 agonist (161) or Flt3 ligand (160). The use of type I IFN as a second adjuvant in a survivin-2B-based vaccine already combined with IFA led to 50% of patients having stable disease versus 20% with IFA only (152).…”
Section: Tumor-associated Antigens and Neoantigens In Crc Vaccinationmentioning
confidence: 99%
“…Detailed information of the study design was described previously. 9 Briefly, this was a phase II, non-randomized, single-arm study in which the HLA-A status was double-blinded. The therapy consisted…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] We previously reported a phase I clinical trial of a peptide vaccine ring finger protein 43 (RNF43) and 34-kDa translocase of the outer mitochondrial membrane (TOMM34) combined with uracil-tegafur (UFT)/LV for patients with metastatic CRC, and demonstrated the safety and immunological responsiveness of this combination therapy. [7][8][9] In this study, we evaluated vaccination-…”
mentioning
confidence: 99%